MAKNA METAFORA DAN SIMILI DALAM SONG OF SOLOMON - Luanmas, Maria Elisabeth (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Metaphor and Simile are two of the figures of speech that take two different things by comparing one with another. The use of metaphor and simile helps speakers or writers to give a clear description throughcomparison or contrast. The writer decided to analyze metaphor and simile figures of speech that use comparison makers such as like, as, as if in Song of Solomon. The problems of this research are focused on the kind and the meaning of metaphor and simile found in Song of Solomon. The aims of the research are to identify, classify, and analyze the forms and the meaning of metaphor and simile in Song of Solomon. The method used in this research is descriptive method. In collecting data, the writer focused on identifying the words, phrases, or parts of sentences. The result showed that the forms of metaphor employed in the verses of Song of Solomon can be categorized as anthropomorfis metaphor, animal metaphor, and sineshetic metaphor, based on Lakoff’s theory, and the simile was analyzed based on Fromilhague’stheory. In terms of the meaning metaphor and simile have similarity and dissimilarity. Similarity in metaphor and simile is the meaning of both figures of speech have the element of comparing two objects. and dissimilarity of metaphor and simile is metaphor does not use the words of comparison, but simile uses the words of comparison such as: like, as, as if. Keywords: Metaphor and Simile Meaning in Song of Solomon